(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is one of the quickest developing nations on the planet, yet, it is famous for its unbending caste system. This paper looks at the historical backdrop of concealment, state of the stifled and starting point of Dalit writings. It incorporates the investigation of development and extent of Dalit literature. Dalit Writings in India problematize dislodged socio-authentic space of underestimated, essential zed classification of individuals having a place with caste-ridden Hindu society of India. Their different subjectivities recover semiotic literary elucidations as respects their contestations, damaged and divided self. Because of solid Dalit movements just as pounding on upper caste society through Dalit literature by writers and masterminds, and furthermore by execution of welfare plots by Government, a positive approach toward fairness is found in social life of Dalit people group these days